South Africa - Bason, T.; Swart, K. (Comparative elite sport development. Systems, structures and public policy, 2025)
South African sport has been shaped by its historical context, with apartheid having a significant influence even after nearly 30 years of democracy. Sport has always been an integral part of society, whether achieving national policy objectives, promoting national unity, transformation and social cohesion, or securing international prestige. Since its readmission to international sport, South Africa has continued to pursue sporting success by hosting mega-events and sports performances on the world stage. South Africa's elite sport has underscored the complexity of sport in the country generally, and specifically in relation to the elite sporting system. With most international elite sport research focused on `developed` nations, this chapter highlights the South Africa case within the context of a `developing` or `emerging` country.